Looking beneath the surface: using hydrogeology and traits to explain flow variability effects on stream macroinvertebrates. Issue 8 (4th May 2016) - Kath, Jarrod; Harrison, Evan; Kefford, Ben J.; Moore, Leah; Wood, Paul J.; Schäfer, Ralf B.; Dyer, Fiona
Abstract: Flow variability drives important instream ecohydrological processes. Nonetheless, generalizations about ecological responses to flow variability are elusive and complicated by interacting factors. Hydrogeological controls on groundwater inputs into streams are often an overlooked factor that may interact with flow variability and influence instream ecology. Flow effects on ecology are also complicated by flora and fauna trait diversity, which makes some organisms more sensitive to flow variability than others. To improve understanding regarding the effects of flow variability on instream communities, we utilized a long‐term 17‐year data set of macroinvertebrate communities from eight sites on the Upper Murrumbidgee River catchment, south eastern Australia. Hydrogeological mapping provided a proxy of groundwater influence on instream ecology. Generalized linear mixed models were used to test hydrogeology (i.e. groundwater influence) and flow variability effects on selected taxa and trait groups. Trait groups tested were those with drought‐resistant life stages, no drought‐resistant life stages and those with poor dispersal traits. Non‐drought resistant and poor dispersing taxa responded to hydrogeology and stream flow variables, while taxa with drought‐resistant traits did not. Poor dispersing taxa displayed the strongest positive response to interactions between high mean flow and hydrogeological conditions that facilitate groundwater inputs. While the importance of flow variability is widely recognized, the combined role of hydrogeology and trait groups on macroinvertebrate responses has not been widely considered thus far. This study demonstrates that the consideration of hydrogeology and faunal traits can help improve the understanding of macroinvertebrate population and community responses to flow regime variability. Copyright © 2016 John Wiley & Sons, Ltd.